THE URGENCY OF DIGITAL VILLAGE DEVELOPMENT TO EMPOWER VILLAGE AUTONOMY - isharyanto (Faculty of Law-Universitas Bandar Lampung, 2024)
Based on Law Number 6 of 2014 concerning Villages, village authority is village autonomy and villages are seen as having a fairly large role in providing public services for the community. Along with the development of information and communication technology, a transformation towards a Digital Village must be carried out. This article is the result of legal doctrine research by prioritizing data in library materials. Sources of information are obtained through regulations and scientific publications that are relevant to the research topic. Based on research, social contractual utilitarianism is the philosophical basis for digital transformation in village government and to realize a Digital Village must meet the following requirements. First, participatory, that is, it is prepared with the agreement of the residents and is in line with development plans in the Regency. Second, there is a need for a legal basis in the form of a Village Regulation on Digital Villages which is in accordance with the village development plan and describes the character that the Village wants to develop. Third, have a road map in the form of stages for developing a Digital Village.